Clinical outcomes in chronic lymphocytic leukaemia associated with expression of CD5, a negative regulator of B‐cell receptor signalling. (8th November 2018) - Friedman, Daphne R.; Guadalupe, Eross; Volkheimer, Alicia; Moore, Joseph O.; Weinberg, J. Brice
Summary: Chronic lymphocytic leukaemia (CLL) is characterized by expression of CD5 on clonal B cells, and is partly driven by activated B‐cell receptor (BCR) signalling. While CD5 is known to be a negative regulator of BCR signalling, it is unknown if variability in CD5 expression exists among patients and whether CLL cell CD5 expression affects CLL clinical outcomes. We assessed the extent to which CD5 expression is correlated with clinical outcomes, and whether this information adds to currently used prognostic markers. We evaluated CD5 expression from 1275 blood samples, established prognostic markers and time to event data from 423 CLL patients followed at the Duke University and Durham VA Medical Centers. CD5 median fluorescence intensity (MFI) was largely stable over time in individual patients, but ranged between 0·5 and 760 in the entire cohort. Lower CD5 MFI was significantly associated with a shorter time to first therapy. CD5 MFI, combined with established clinical and molecular prognostic markers, significantly improved risk‐stratification. CD5 may affect disease outcomes by suppressing signalling through the BCR. Thus, a strategy to modulate CLL cell CD5 expression or function could be a therapeutic approach in CLL.